Roles of Bacterial Mechanosensitive Channels in Infection and Antibiotic Susceptibility - Margareth Sidarta; Luna Baruah; Michaela Wenzel (MDPI AG, 2022)
Bacteria accumulate osmolytes to prevent cell dehydration during hyperosmotic stress. A sudden change to a hypotonic environment leads to a rapid water influx, causing swelling of the protoplast. To prevent cell lysis through osmotic bursting, mechanosensitive channels detect changes in turgor pressure and act as emergency-release valves for the ions and osmolytes, restoring the osmotic balance. This adaptation mechanism is well-characterized with respect to the osmotic challenges bacteria face in environments such as soil or an aquatic habitat. However, mechanosensitive channels also play a role during infection, e.g., during host colonization or release into environmental reservoirs. Moreover, recent studies have proposed roles for mechanosensitive channels as determinants of antibiotic susceptibility. Interestingly, some studies suggest that they serve as entry gates for antimicrobials into cells, enhancing antibiotic efficiency, while others propose that they play a role in antibiotic-stress adaptation, reducing susceptibility to certain antimicrobials. These findings suggest different facets regarding the relevance of mechanosensitive channels during infection and antibiotic exposure as well as illustrate that they may be interesting targets for antibacterial chemotherapy. Here, we summarize the recent findings on the relevance of mechanosensitive channels for bacterial infections, including transitioning between host and environment, virulence, and susceptibility to antimicrobials, and discuss their potential as antibacterial drug targets.